Digital Posyandu for Community-Based Maternal and Child ‎Health Information Management Education: An Offline ‎Application to Strengthen Cadre Digital Literacy and Service ‎Efficiency - Ikhsan Ikhsan; Kani Kani (Yayasan Darussalam Bengkulu, 2026)
Posyandu (Integrated Health Service Post) is a community-based platform for maternal and child health services, yet manual recording can constrain data quality, reporting timeliness, and routine monitoring. This community-engaged implementation evaluation developed and field-tested an offline digital Posyandu application across 12 Posyandu sites in Rawakalong Village. The system integrates records for children under five and pregnant women, growth monitoring, immunization scheduling, monthly reporting, and local data storage. Development proceeded through needs assessment, iterative system refinement, functional testing, cadre validation, training, and field monitoring. Pre- and post-training evaluation recorded an 80% increase in cadre digital-literacy performance. During implementation, recording speed increased by 63%, data-entry errors decreased by 45%, and monthly reporting time was reduced from three to five days to less than 24 hours. The findings indicate that an offline, locally deployable digital health-information system can support cadre capacity and improve operational efficiency in community-based maternal and child health services. Because the evaluation did not directly measure parental health literacy or child-development outcomes, the contribution is interpreted in terms of information management, cadre digital literacy, and service efficiency rather than direct parent- or child-level effects.